Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,4x^4+4x^3-x^2-x=4x^3\left(x+1\right)-x\left(x+1\right)\)
\(=\left(x+1\right)\left(4x^3-x\right)\)
\(=x\left(x+1\right)\left(4x^2-1\right)\)
\(=x\left(x+1\right)\left(2x-1\right)\left(2x+1\right)\)
\(\frac{x^4+x^3-x^2-2x-2}{x^4+2x^3-x^2-4x-2}=\frac{\left(x^4-x^2-2\right)+\left(x^3-2x\right)}{\left(x^4-x^2-2\right)+\left(2x^3-4x\right)}\)
\(=\frac{\left(x^2-2\right)\left(x^2+1\right)+x\left(x^2-2\right)}{\left(x^2-2\right)\left(x^2+1\right)+2x\left(x^2-2\right)}=\frac{\left(x^2-2\right)\left(x^2+x+1\right)}{\left(x^2-2\right)\left(x^2+2x+1\right)}\)
\(=\frac{x^2+x+1}{\left(x+1\right)^2}\)
\(F\left(x\right)=\frac{x^4+x^3-x^2-2x-2}{x^4+2x^3-x^2-4x-2}\)
\(=\frac{\left(x^4+x^3+x^2\right)-2x^2-2x-2}{\left(x^4+2x^3+x^2\right)-\left(2x^2+4x+2\right)}\)
\(=\frac{x^2\left(x^2+x+1\right)-2\left(x^2+x+1\right)}{x^2\left(x^2+2x+1\right)-2\left(x^2+2x+1\right)}=\frac{x^2+x+1}{x^2+2x+1}\)
\(x^8+x^4+1\)
\(=\left(x^8+2x^4+1\right)-x^4\)
\(=\left(x^4+1\right)^2-x^4\)
\(=\left(x^4+1-x^2\right)\left(x^4+1+x^2\right)\)
\(=\left(x^4-x^2+1\right)\left(x^4+2x^2-x^2+1\right)\)
\(=\left(x^4-x^2+1\right)[\left(x^2+1\right)^2-x^2]\)
\(=\left(x^4-x^2+1\right)\left(x^2+1-x\right)\left(x^2+1+x\right)\)